Production of hyaluronic acid by Streptococcus zooepidemicus on protein substrates obtained from Scyliorhinus canicula discards - Vásquez, José A. (2015)
This work investigates the production of hyaluronic acid (H) by Streptococcus equi subsp. zooepidemicus in complex media formulated with peptones obtained from Scyliorhinus canicula viscera by-products. Initially, in batch cultures, the greatest productions were achieved using commercial media (3.03 g/L) followed by peptones from alcalase hydrolyzed viscera (2.32 g/L) and peptones from non-hydrolyzed viscera (2.26 g/L). An increase of between 12% and 15% was found in subsequent fed-batch cultures performed on waste peptones. Such organic nitrogen sources were shown to be an excellent low-cost substrate for microbial H, saving more than 50% of the nutrient costs.